Site-specific Surgical Site Infection Rates for Rib-based Distraction. Issue 9 (October 2019) - Striano, Brendan M.; Refakis, Christian A.; Anari, Jason B.; Campbell, Robert M.; Flynn, John M.
Abstract : Background: Implantable rib-based distraction devices have revolutionized the treatment of children with early onset scoliosis and thoracic insufficiency syndrome. Unfortunately, the need for multiple skin incisions and repeated surgeries in a fragile patient population creates considerable infection risk. In order to assess rates of infection for different incision locations and potential risk factors, we generated a prospectively collected database of patients treated with rib-based distraction devices. Methods: We analyzed a cohort of patients with thoracic insufficiency syndrome from various etiologies that our institution treated with rib-based distraction devices from 2013 to 2016. Surgery type (implantation, expansion, revision/removal), and surgeon adjudicated surgical site infection (SSI) were collected. For this study, we developed a novel, rib-based distraction device surgical site labeling system in which incisions could be labeled as either proximal or distal surgical exposure areas. Treating surgeons documented the operative site, procedure, and SSI site in real-time. Results: A total of 166 unique patients underwent 670 procedures during the study period, producing 1537 evaluable surgical sites; 1299 proximal and 238 distal. Patients were 6.81±4.0 years of age on average. Forty-seven procedures documented SSIs (7.0%), while 40 (24.1%) patients experienced an infection. Analysis showed significant variation in the rate of infection between implantation, and expansion, and revision procedures, with implantation procedures having the highest infection rate at 13.1% ( P <0.01). Infections occurred more frequently at distal sites than proximal ones ( P =0.02). Conclusions: Our novel, surgeon-entered, prospective quality improvement database has identified distal surgical sites as being at higher risk for SSI than proximal ones. Further, rib-based distraction device implantation procedures were identified as being at a greater risk for SSI than expansion or revision procedures. We believe this data can lead to improved prevention measures, anticipatory guidance, and patient care. Level of Evidence: Level II—prognostic study.